1976
DOI: 10.1111/j.1469-8137.1976.tb01434.x
|View full text |Cite
|
Sign up to set email alerts
|

Waterlogging and Petiole Epinasty in Tomato: The Role of Ethylene and Low Oxygen

Abstract: SUMMARY Waterlogging the soil promotes epinastic growth of tomato petioles and increases the concentration of ethylene which can be extracted from various parts of the shoot. These concentrations exceed those normally required to promote epinasty when applied to the shoots of non‐waterlogged plants. Waterlogging also results in a rapid decline in the concentration of dissolved oxygen in the soil water. Low concentrations of oxygen around the roots of plants growing in nutrient solution promote epinastic growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(60 citation statements)
references
References 20 publications
2
58
0
Order By: Relevance
“…The high production and accumulation of ethylene in shoots results from the high ACC levels, synthesized in roots by ACC synthase, then transported from the root system to shoot where it is converted to ethylene by ACC oxidase (Bradford et al 1982). Since oxygen concentrations of waterlogged root systems are too low or nonexistent, the conversion of ACC to ethylene by ACC oxidase cannot take place (Jackson and Campbell 1976;Bradford and Dilley 1978;Wang and Arteca 1992;Banga et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The high production and accumulation of ethylene in shoots results from the high ACC levels, synthesized in roots by ACC synthase, then transported from the root system to shoot where it is converted to ethylene by ACC oxidase (Bradford et al 1982). Since oxygen concentrations of waterlogged root systems are too low or nonexistent, the conversion of ACC to ethylene by ACC oxidase cannot take place (Jackson and Campbell 1976;Bradford and Dilley 1978;Wang and Arteca 1992;Banga et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Waterlogging been reported to cause elevated ethylene levels and epinasty in the shoot regardless of whether the condition is imposed by waterlogging or by flushing with N2 (4,12,14). It has been shown that ethylene production by maize (Zea mays L.) roots exposed to 5 kPa oxygen was inhibited by AVG supplemented to the nutrient solution and this also reduced aerenchyma formation (13).…”
Section: Introductionmentioning
confidence: 99%
“…Under aeration, AOA stimulated ACC synthase activity in both the roots and leaves. However, in combination with low 02 conditions, AOA caused a stimulation in ACC synthase activity in the leaves and no effect in the roots.Ethylene production is observed in all higher plants, where it is involved in numerous aspects of plant growth and development but most notably as a response to stress conditions (1).Waterlogging been reported to cause elevated ethylene levels and epinasty in the shoot regardless of whether the condition is imposed by waterlogging or by flushing with N2 (4,12,14). It has been shown that ethylene production by maize (Zea mays L.) roots exposed to 5 kPa oxygen was inhibited by AVG supplemented to the nutrient solution and this also reduced aerenchyma formation (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ethylene is a second phytohormone that might be involved in leaf epinasty, for the main reason that it can cause differential growth, in terms of petiole epinasty (Jackson and Campbell, 1976;Reid et al, 1981;El-Iklil et al, 2000) or an exaggerated apical hook (Guzman and Ecker, 1990;Stepanova and Alonso, 2005). Other than affecting the sinksource balance, disbudding might enhance ethylene production, since plants are wounded which may cause an increase in ethylene production (Druege, 2006).…”
Section: Involvement Of Phytohormonesmentioning
confidence: 99%